The role of zooplankton as food in carp pond farming: a review. (14th July 2015) - Anton‐Pardo, M.; Adámek, Z.
Summary: This review paper aims to offer a current view on the function of zooplankton as food for common carp, as traditionally its role has been underestimated compared with benthic invertebrates or supplementary feeding. We prove the importance of zooplankton organisms in the life cycle of common carp in fishponds. As in other fish species, carp larvae feed mainly on zooplankton, starting with small organisms (rotifers) and as they grow then shifting to larger organisms, e.g. copepods and cladocerans. As adults they are commonly benthic feeders, concentrating principally on zoobenthos (mainly chironomid larvae); however, zooplankton is also an important part of the diet, depending on food availability and spatial and temporal variation. Zooplankton is high in protein (above 50% of dry matter for some groups) and lipids (approximately 10% of dry matter with a significant proportion of unsaturated fatty acids). Natural food therefore may provide a high nutritional content, compared to other diets. Appropriate management strategies in fishponds can potentially increase the production of zooplankton, e.g. monitoring zooplankton levels and stocking fish at the appropriate moment, control of environmental variables favouring zooplankton development, and utilizing sustainable fish stocking densities.